Comparative analysis of Chlamydia pneumoniae pneumonia (CPP) and Mycoplasma pneumoniae pneumonia in children and risk factors of severe CPP - Yu HUANG; Yi CHEN; Min LIU; Lan-Fang TANG; Lan-Fang TANG (BMC Infectious Diseases)
Abstract Background Chlamydia penumoniae (CP) pneumonia (CPP) in children often receives less clinical attention due to its relatively mild presentation. This study comparatively analyzed CPP and Mycoplasma pneumoniae pneumonia (MPP), and investigated risk factors for severe CPP. Methods A retrospective analysis was conducted on 176 CPP patients and 176 concurrently hospitalized MPP patients during the same period to compare clinical features. CPP cases were further stratified into severe and mild subgroup to identify risk factors. Results The number of hospitalized children with CPP increased in 2024 compared to 2023, with a significant surge observed from December 2024 to February 2025. CPP patients were significantly older than MPP patients (mean age: 10.53 ± 2.89 vs. 6.68 ± 2.88, p < 0.05) and exhibited longer durations of cough and higher rates of chest pain (p < 0.05). Laboratory findings revealed significantly elevated white blood cell (WBC) and eosinophil (EOS) counts in CPP versus MPP (p < 0.05). Severe CPP accounted for 6.8% of cases, and binary logistic regression identified eosinophil count as a potential biomarker for severe CPP (p < 0.05). Conclusions The number of hospitalized children with CPP increased in 2024 compared to 2023. CPP manifested more prominent cough and chest pain symptoms compared to MPP patients. EOS count levels may serve as a potential biomarker of severe CPP.